2012
DOI: 10.7307/ptt.v22i2.168
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of Maintenance Approach for Improved Operability and Safety of Ship Navigation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Аналіз даних може допомогти оцінити надійність суднових двигунів і спланувати заходи з технічного обслуговування, що потенційно зменшить кількість відмов двигунів і аварій в судноплавній галузі [9]. Модель коригування технічного обслуговування складається з аналізу експлуатаційних даних та аналізу ризиків, визначення важливих компонентів та прийняття ефективної політики технічного обслуговування [10].…”
Section: вступunclassified
“…Аналіз даних може допомогти оцінити надійність суднових двигунів і спланувати заходи з технічного обслуговування, що потенційно зменшить кількість відмов двигунів і аварій в судноплавній галузі [9]. Модель коригування технічного обслуговування складається з аналізу експлуатаційних даних та аналізу ризиків, визначення важливих компонентів та прийняття ефективної політики технічного обслуговування [10].…”
Section: вступunclassified
“…In general, components with the most frequent operational failures are selected for this analysis. For example, the study in [14] examined maintenance adjustments for exhaust valves, while the work in [15] focused on air compressors, and it was found that the frequency of failure and the maintenance costs could be reduced by changing the initial maintenance schedule. To achieve a relevant and meaningful change in the maintenance plan, it is necessary to obtain a reliable database (maintenance history) of the component under study.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, maintenance data and failures after the change of intervals were analysed to determine the actual eff ect of the performed change and its justifi cation. Adjustment of the maintenance approach based on the real operational data [1], [6] is more reliable than the design of the initial maintenance concept for a new ship.…”
Section: Introduction /Uvodmentioning
confidence: 99%